RDM: An Approach from a Modern University with a Growing Research Portfolio - Alistair Fitt; Rowena Rouse; Sarah Taylor (International Journal of Digital Curation, 2015)
This article describes the background work undertaken by Oxford Brookes University in assessing how best to position institutional support for Research Data Management. It further discusses the development of our University’s research data management policy and its collaborative approach to data management support. Finally, it reflects on the challenges of overseeing policy implementation and providing the required enactment infrastructure. The approach that we take is one that will hopefully be of interest to those institutions who are developing their research base and seeking to offer better data management support to researchers in a time of reduced or declining resource. Overall, we feel that the strategic and institution-wide approach that we have taken has worked well, and may be suited to institutions like ours that are less research-intensive. Finally, we feel that our approach is one that can readily be copied.